Examining tactical sprint actions and distribution among playing positions attending to match status in soccer: Implications for specific training - Lobo-Triviño, D.; García-Calvo, T.; Manzano-Rodríguez, D.; Nevado, F.; Chena, M.; Piñero-Madrona, J. Á.; Martín-Ardila, E.; Raya-González, J. (PLOS ONE, 2024)
The study aimed to analyze the tactical sprint actions performed by Spanish professional soccer players, considering their playing positions and the match status at the time of each action. Thirty-two Spanish male professional soccer players from a LaLiga Spanish Second Division (LaLiga SmarthBank) team participated in this study. Actions above 85% of the players` maximum velocity during 42 official matches were collected by an optical tracking system ChyronHego® and were synchronized using Mediacoach software (LaLiga, Madrid, Spain). Then, actios were analyzed trough an observation instrument designed to assess the type of tactical action performed by players. Central defenders (CD) and wide defenders (WD) were mainly involved in recovery runs. Central midfielders (CM) also frequently performed recovery runs and pressing actions. Wide midfielders (WM) were often engaged in runs in behind/penetrate actions, while forwards (F) had a diverse range of sprint actions, including pressing, runs in behind/penetrate, and breaking into the box. It was observed that F performed fewer chase actions than expected. On the other hand, CD, WD, and CM engaged in a greater number of recovery run actions than expected. CD also performed more close down/interception actions than expected, while CM, WM, and F performed fewer close down/interception actions than expected. When their team was losing, WM performed more recovery run actions than expected. CM made more runs with the ball when their team was winning CD showed a higher frequency of breaks into the box when their team was winning. These findings provide valuable information regarding the tactical aspects of sprinting in soccer, facilitating the design of specific training tasks that not only address the physical demands associated with each playing position but also considering the tactical context in which sprints occur.